The Relationship between Flexible Working Arrangements and Quality of Work Life among Academicians in a Selected Public Institution of Higher Learning in Kuching, Sarawak, Malaysia - Diyanna Nurqistyna, Ariffin; Nur Fatihah, Abdullah Bandar; Surena, Sabil; Samsiah, Jayos; Mazdan, Ali Amaran; Rozita, Hamdan (Faculty of Cognitive Sciences & Human Development UNIMAS, 2016)
This study aims to determine the relationship between working arrangements and quality of work life (QWL) among academicians in a selected public institution of higher learning in Kuching, Sarawak. A survey methodology was used in this study. This research involves the utilization of questionnaire which was administered among one-hundred and fifty (151) academicians currently working in a selected public institution in Kuching, Sarawak. The relationship between flexible working arrangements and quality of work life was analyzed using the Pearson’s Correlation analysis test. The results of this study revealed that there is a significant relationship between long working arrangement and flexible working arrangements with QWL. Hence, if organizations are concerned about developing their human resources and gaining a competitive advantage in the marketplace, it is necessary that they attend to one of their most precious assets, namely, their human resources by practicing flexible working arrangements.